2008
DOI: 10.1007/s00423-008-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-focused results after laparoscopic fundoplication for refractory gastroesophageal reflux disease—a prospective study

Abstract: Laparoscopic fundoplication seems to be an effective treatment for severe, drug-resistant GERD. The high patient satisfaction rate and the positive therapeutic response in 95% of patients justify this procedure in this strictly selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Pain and disfigurement are much less, and it allows better cosmesis, shortened recovery time and quicker return to preoperative well-being and normal activity [3]. Despite the minimally invasive nature of laparoscopy, host physiologic responses to stress are yet invariably activated.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Pain and disfigurement are much less, and it allows better cosmesis, shortened recovery time and quicker return to preoperative well-being and normal activity [3]. Despite the minimally invasive nature of laparoscopy, host physiologic responses to stress are yet invariably activated.…”
Section: Discussionmentioning
confidence: 96%
“…The overall results on postoperative outcome have either been positive in favor of the glucocorticoid group or without differences between study groups, with postoperative nausea and vomiting and pain outcome parameters most significantly improved [5][6][7]. Data from LFNF have shown questionable effects on pain, nausea and vomiting [3], but show greater satisfaction and shorter stay in the day care unit [8].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…1927 In 3 studies, symptoms improved as measured by GERD-HRQL score from 18.6–25 to 1.6–5. 20, 22, 23 At 10 years, Broeders et al reported resolution or improvement of symptoms in 92.4% of patients.…”
Section: Resultsmentioning
confidence: 99%